Study Design in Medical Research (Ibrahim Cardiac Medical Journal, 2012)
An appropriate study design is key to answer the research question or to test the hypothesis of a study. A study design is, in fact, how a study can be conducted in a given situation. A study design is more important than analysis of data, for a faulty study design can never be retrieved once it is applied, whereas a poorly analysed study can be retrieved and reanalyzed if needed. Therefore, appropriate study design is an effective way to draw a meaningful conclusion from the research data. Here we highlight the key concept of study design, their types and formulating a study design based on research question and hypothesis.Ibrahim Cardiac Med J 2012; 2(2): 41-47